PERBANDINGAN REGRESI LINIER BERGANDA DENGAN SPLINE TRUNCATED (STUDI KASUS: KEMISKINAN DI PROVINSI PAPUA) - Ni Putu Ayu Mirah Mariati; I Wayan Sudiarsa; Ni Made Sukma Sanjiwani (Widyadari : Jurnal Pendidikan, 2022)
Regression analysis was used to study the pattern of the relationship between the response variable and the predictor variable. There are two approaches used in this method, namely parametric and nonparametric. The most popular parametric regression used is multiple linear regression. In addition to parametric regression there are nonparametric regression approaches. One of the well-known nonparametric regression is Spline Truncated. This research to compare the multiple linear regression method with the Spline Truncated in the case of poverty in Papua Province. Based on the results of research on poverty cases in Papua Province, it can be concluded that the Spline Truncated regression is better than the multiple linear regression with R2 of 88.39%.